2021
DOI: 10.1001/jamaoto.2020.4352
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hearing Impairment and Changes in Pure-Tone Average Across Generations

Abstract: IMPORTANCE Age-adjusted prevalence of hearing impairment (HI) decreased across generations in the 20th century, suggesting that HI is partially preventable. It is not known whether HI incidence differs by generation. OBJECTIVES To examine whether HI incidence and change in pure-tone average (PTA) differ by generation and identify factors underlying these differences. DESIGN, SETTING, AND PARTICIPANTSThis cohort study used data from the Epidemiology of Hearing Loss Study (EHLS) and Beaver Dam Offspring Study (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…The incidence rates reported in this study were comparable with previous studies. 37 38 39 40 41 42 43 44 45 For instance, the incidence rate of cognitive impairment was 52.6 cases/1000 person-years in a 5-year follow-up study of Aboriginal Australians aged over 60 years, 46 which is similar to our result (64.6 cases/1000 person-years). The observed sex- and age-disparities in incidence rates also corresponded to prior knowledge.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The incidence rates reported in this study were comparable with previous studies. 37 38 39 40 41 42 43 44 45 For instance, the incidence rate of cognitive impairment was 52.6 cases/1000 person-years in a 5-year follow-up study of Aboriginal Australians aged over 60 years, 46 which is similar to our result (64.6 cases/1000 person-years). The observed sex- and age-disparities in incidence rates also corresponded to prior knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…41 Also, our results echoed the established knowledge that the risk of impairments in sensory, physical, and cognitive function was higher in older ages. 40 42 43 46 47 48 Other than confirming previous findings, our study added valuable evidence of age- and sex-specific incidence rates of AFRIs in a wide range of age groups (51-90 years) within a cohort, which provided important evidence for the prevention of ARFIs in the aging era.…”
Section: Discussionsupporting
confidence: 81%
“… 22 , 24 , 27 , 28 , 29 For example, a review reported that women had a greater incidence of depression than men, and the incidence rate decreased after the age of 50 years Also, our results echoed the established knowledge that the risk of impairments in sensory, physical, and cognitive function was higher in older ages. 23 , 25 , 30 , 31 , 32 Compared to other ARFIs, the exponential increase periods for restless sleep and depression traits may have occurred earlier and may have higher incidence in the middle-aged population. 24 Therefore, our observation that their incidence rate increased less rapidly in older adults should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 97%
“…Across both cohorts, 59 participants (EHLS, n = 51; BOSS, n = 8) did not have audiometric data so were not included in this study. Previous studies have pooled samples from EHLS and BOSS cohorts (Fischer et al, 2017; Paulsen et al, 2021).…”
Section: Methodsmentioning
confidence: 99%